Analysis of Halth Workers’ Satisfaction with Electronic Medical Records at Cililin Hospital - Erix Gunawan; Bagus Irfan Purkon (Greenation Publisher & Yayasan Global Research National, 2025)
The use of Electronic Medical Records (RME) is an important part of the process of digitizing health services which requires the active participation of health workers as the main users. This study aims to explore the perception of health workers on the implementation of RME at Cililin Hospital and its relationship with job satisfaction levels. The study used a qualitative method with a phenomenological approach, involving 50 respondents who were purposively selected from a total of 200 health workers. Data was obtained through in-depth interviews and observations, then analyzed using thematic analysis techniques to identify the main themes of the respondents' experiences. The results showed that most health workers showed a positive perception of the use of RME (86.53%) and expressed satisfaction with the system (88%), with a significant relationship between perception and satisfaction (p-value = 0.005). Factors that affect positive perceptions include improving work efficiency, data accuracy and security, and ease of access to information, while the main obstacles are related to the limitations of network infrastructure and the need for continuous training. This study concludes that the perception of health workers plays a crucial role in determining RME acceptance, in accordance with the Technology Acceptance Model framework. The theoretical contribution of this research lies in strengthening the study of the acceptance of technology in the health sector, while its practical contribution provides direction for hospital management and policymakers to expand training programs, improve digital infrastructure support, and improve internal communication. The research recommendations emphasize the importance of policies that are responsive to local conditions and the need for follow-up studies with wider hospital coverage to make the results more representative.